Evaluation of Megabruchidius tonkineus (Coleoptera: Chrysomelidae: Bruchinae), a candidate biological control agent for Gleditsia triacanthos L. (Fabaceae) in South Africa - Salgado Astudillo, Sara Elizabeth (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Gleditsia triacanthos L. (Fabaceae) (honey locust) is a fast-growing, deciduous tree indigenous to the United States of America. Introduced around the world as an ornamental tree, it has become invasive in a number of countries. Where it is invasive, G. triacanthos competes and replaces indigenous species; it creates dense stands along watercourses, posing a significant environmental threat. In South Africa, G. triacanthos is regarded as one of the country's fastest spreading weeds. Gleditsia triacanthos produces numerous seeds contained in large hanging pods. Once dislodged from the pods, the seeds are dispersed by birds and mammals, including livestock, which eat the pods. It has been suggested that the seeds should be the target for biological control programme. Some invasive alien plant species are characterised by their ability to spread and establish in new ecosystems because they tolerate a wide range of environmental conditions. In order to predict areas of likely invasion, species distribution models (SDMs) are used to identify areas climatically suitable for their invasion, so enabling better targeted control of the plant species. Gleditsia triacanthos adapts to a wide range of climates and soil types, and tolerates salinity, drought and frost. Currently primarily restricted to the Grassland Biome of South Africa, G. triacanthos has doubled its distribution area in the past 15 years, and it is not known how far the species will spread. In this study we used two different modelling programmes, CLIMEX and MaxEnt, to predict areas where G. triacanthos could find favourable growing conditions; both SDMs showed that most of the country is suitable for G. triacanthos and that it will probably continue to spread, if left unmanaged, into new bioregions, such as the Karoo. In South Africa, the Asian seed-feeding bruchid, Megabruchidius tonkineus (Pic, 1914) (Coleoptera: Chrysomelidae: Bruchinae) has been recorded in the plant's seed pods and has been considered as a biological control agent. The insect was not released as part of a formal biological control programme and neither host-specificity nor impact studies were conducted on the species prior to its discovery. In 2017 a decision was made to re-consider its status as a Abstract biological control agent until further details of its biology, host specificity, and impact on the seeds of G. triacanthos in South Africa were available. This study shows that Megabruchidius tonkineus has established across the entire G. triacanthos population in South Africa damaging approximately 9% of seeds. Laboratory studies show that, Megabruchidius tonkineus completes its larval development in the seeds of G. triacanthos in about 66.80 Â± 0.6880 SE days before eclosing. In addition, the adult females oviposit on the following Fabaceae species: Arachis hypogaea, Albizia, julibrissin, Cicer arietinum, Pisum sativum, Dipogon lignosus, Peltophorum africanum, Podalyria buxifolia Senegalia burkei, Umtiza listerina and Vachellia sieberiana. However, larval development was limited to G. triacanthos. It is concluded that the seed-feeding beetle is not a threat to native Fabaceae species in South Africa, however, it does not damage enough G. triacanthos seeds to be considered a valuable biological control agent at this stage, and additional seed-feeding biological control agents should be considered to reduce the number of G. triacanthos seeds entering the environment.
Keywords: Honey locust -- South Africa; Honey locust Biological control -- South Africa; Invasive plants Biological control -- South Africa; Biogeography -- South Africa; Biogeography Climatic factors -- South Africa; Megabruchidius tonkineus -- South Africa